Semantic Groups of Vocabulary in Sports Reports - Barseghyan, Gevorg (Armenian Folia Anglistika, 2020)
Nowadays sports as a separate component of social life includes a great many varieties which enable millions of sportsmen and fans to communicate with one another. Thorough research is carried out on various aspects of sport: from the philosophy of sports to exquisite psychological observations of individual sportmen. Thus the study of the forms and the style of sports reports as well as their linguostylistic peculiarities has become an imperative. The aim of our research is to reveal the characteristic features of sports reports with reference to the vocabulary used, namely – the semantic groups most frequently occurring in sports speech.